2021
DOI: 10.1002/essoar.10507881.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced Rainfall in Future Heavy Precipitation Events Related to Contracted Rain Area Despite Increased Rain Rate

Abstract: Expected impacts of climate change on rainfall during heavy precipitation events (HPEs) have the potential to significantly alter their influence on future populations. Where precipitation variability is high, such as in Mediterranean and arid climates, the impact of individual HPEs in terms of both peril (e.g.,

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
1
2
0
Order By: Relevance
“…(1) the total number of objects increases in (almost) all cases, (2) future objects have larger areas and volumes, regardless of how long they live or how intense they are, (3) despite this, objects of all areas and lifetimes have lower mean intensities, (4) it can thus be concluded that the increase in P tot is driven by the combined effect of more objects and an increase in the area of these objects, (5) the increase in object volumes despite a decrease in intensity shows that the effects of more objects and higher areas are dominant over the reduction in mean object intensity, which acts in the opposing direction. A final note would be that the area of the most intense objects is actually found to decrease (-6 %) and their maximum local precipitation intensity found to increase (+12 %), in agreement with the findings of Armon et al (2022) and Caldas-Alvarez et al (2022). Aided by the growing use of kilometre-scale climate models (Lucas-Picher et al, 2021), Lagrangian methods for analysing the response of convective precipitation to climate change have become increasingly popular (e.g.…”
Section: Results Ii: Future Projectionssupporting
confidence: 87%
“…(1) the total number of objects increases in (almost) all cases, (2) future objects have larger areas and volumes, regardless of how long they live or how intense they are, (3) despite this, objects of all areas and lifetimes have lower mean intensities, (4) it can thus be concluded that the increase in P tot is driven by the combined effect of more objects and an increase in the area of these objects, (5) the increase in object volumes despite a decrease in intensity shows that the effects of more objects and higher areas are dominant over the reduction in mean object intensity, which acts in the opposing direction. A final note would be that the area of the most intense objects is actually found to decrease (-6 %) and their maximum local precipitation intensity found to increase (+12 %), in agreement with the findings of Armon et al (2022) and Caldas-Alvarez et al (2022). Aided by the growing use of kilometre-scale climate models (Lucas-Picher et al, 2021), Lagrangian methods for analysing the response of convective precipitation to climate change have become increasingly popular (e.g.…”
Section: Results Ii: Future Projectionssupporting
confidence: 87%
“…In other words, such changes obscure the interpretation of the results. Several studies (Armon et al., 2022; Hibino et al., 2018; Kawase et al., 2020, 2021; Pall et al., 2017) have found that there is a decrease in convective and/or total rainfall amounts in simulations where a PGW approach was applied. It is unclear if this is associated with a change in vertical structure that may dampen the convective mechanisms associated with the original event as it was proposed by for example, Hibino et al.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, previous studies have explored alternative methods for studying climate change impacts on convective events. There are commonly two approaches: event‐driven (Armon et al., 2022; Hibino et al., 2018; Kawase et al., 2020, 2021; Lackmann, 2013; Takayabu et al., 2015) and climatological (Kawase et al., 2019; Lenderink et al., 2021; Liu et al., 2017; Prein, Rasmussen, et al., 2017). The former focuses on the study of a specific event under different conditions related to climate change, while the latter focuses on the general changes of this type of event on a climatological time scale.…”
Section: Introductionmentioning
confidence: 99%